Detecting isolated superior mesenteric artery dissection with computed tomography - Özgül, Esra (Journal of Surgery and Medicine, 2020)
Aim: Isolated superior mesenteric artery (SMA) dissection without associated aortic dissection is a rare entity. The aim of the study is to evaluate its incidence, and multidetector computed tomography (MDCT) and computed tomography angiography (CTA) findings, as well as show the clinical importance of this condition, which should be diagnosed and treated urgently. Methods: Images of all patients who underwent contrast enhanced CTA or MDCT scan from July 2017 to July 2020 at our radiology department were examined retrospectively. A total of 600 CTA and 14000 contrast enhanced MDCT scans (14600 CT) were evaluated. Only the cases with isolated SMA dissections without aortic involvement, who had arterial phases on contrast enhanced MDCT images, were included. Aortic dissection cases with SMA involvement, and non-contrast MDCT images were excluded. Age, gender, symptoms, presence of thrombosis or bowel ischemia were noted. Average extension of dissection and distance from origin were measured. Results: Ten patients (7 M, 3 F), aged between 48-66 years (mean: 57 years), had isolated SMA dissection. The mean distance of dissection from origin and mean extension were 1.9 cm and 3.4 cm, respectively. Patients were treated with conservative anticoagulation therapy. Follow-up CTA or MDCT showed normal SMA without evidence of dissection in 5 patients, decreased extension and length of dissection in 3 patients and no significant difference in 2 patients. Conclusion: Isolated SMA dissection is a rare but important cause of abdominal pain. Early diagnosis allows correct treatment. CT is a useful noninvasive method for diagnosis and anticoagulation therapy is successful.